Environmental benefits of circular economy approach to use of cobalt. (September 2022) - Rahimpour Golroudbary, Saeed; Farfan, Javier; Lohrmann, Alena; Kraslawski, Andrzej
Highlights: Cobalt recycling leads to 46% lower energy consumption than primary production. Cobalt recycling leads to 40% reduction in the use of water than primary production. Recycling contributes to mitigation of GHG emissions of cobalt flow by 59%. Recycling contributes to mitigation of SOx emissions of cobalt flow by 98%. Around 25% of required cobalt could be supplied from secondary sources by 2050. Abstract: Cobalt is an important critical material and a constituent of a broad range of products such as batteries, electronics, superalloys, and hard metals. Effective recycling of cobalt is considered one of the most pivotal processes in alleviating its criticality. In this paper, using the dynamic modelling of material, energy, and water flows in cobalt supply chain, we show that by 2050 around 25% of the total demand for cobalt could be supplied by recycling. Our results indicate that, compared to the primary production of cobalt, its recycling might lead to a reduction of energy consumption by 46% associated with the global cobalt supply chain and the corresponding fall in the use of water by 40%. In addition, recycling of cobalt is estimated to mitigate around 59% of the total emissions of greenhouse gases and 98% of the total emissions of sulfur oxides. Finally, we present the regionally distributed projections of cobalt-related energy and water use from 2020 to 2050.